TWISTED INTRAMOLECULAR CHARGE TRANSFER IN STYRYLPENTAFLUOROPHENYL AMINOPYRENE: A DFT AND TDDFT STUDY OF SOLVENT EFFECTS AND MOLECULAR TWISTING DYNAMICS - Maftuhin, Wafa; Walter, Michael (Indonesian Physical Review, 2026)
Twisted intramolecular charge transfer is a key feature of donor–acceptor chromophores, significantly influencing their photophysical behavior. These processes are also central to the design of sensing and optoelectronic materials. In this study, we examine styrylpentafluorophenyl aminopyrene, which links a rigid pentafluorostyryl acceptor to a flexible N, N-dimethylaniline donor. Using density functional theory (DFT) and time-dependent DFT, we optimized ground and excited-state structures, mapped torsional energy surfaces, and explored solvent effects within a dielectric continuum model. The calculations indicate that the pentafluorostyryl unit remains locked in conjugation, while donor twisting through the dimethylaniline group drives the formation of a twisted intramolecular charge transfer (TICT) state. This mechanism reproduces observed solvent-independent absorption and solvent-sensitive fluorescence shifts of about 0.5 eV in polar media. The results place styrylpentafluorophenyl aminopyrene among donor-controlled twisted intramolecular charge transfer systems, while also highlighting how the structural asymmetry of a rigid acceptor and a flexible donor creates a single relaxation pathway. Such design principles can help guide the tuning of charge-transfer emission in functional dyes and related optoelectronic applications. In contrast to previously studied systems, styrylpentafluorophenyl aminopyrene reveals a distinctly donor-controlled mechanism reinforced by a rigid acceptor, establishing a new theoretical basis for predicting twisted intramolecular charge transfer behavior in asymmetric donor–acceptor chromophores.